2015
DOI: 10.2337/db14-0988
|View full text |Cite
|
Sign up to set email alerts
|

Age- and Sex-Specific Causal Effects of Adiposity on Cardiovascular Risk Factors

Abstract: Observational studies have reported different effects of adiposity on cardiovascular risk factors across age and sex. Since cardiovascular risk factors are enriched in obese individuals, it has not been easy to dissect the effects of adiposity from those of other risk factors. We used a Mendelian randomization approach, applying a set of 32 genetic markers to estimate the causal effect of adiposity on blood pressure, glycemic indices, circulating lipid levels, and markers of inflammation and liver disease in u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
51
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(68 citation statements)
references
References 38 publications
11
51
1
1
Order By: Relevance
“…A similar report was found in Fall et al [3] which stated that they observed larger regression coefficients in men than in women for associations of BMI with systolic and diastolic blood pressure and levels of total cholesterol, triglycerides, alkaline transaminase, gama glutamate transaminase, and fasting insulin. Hence, men may have more risk than women.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…A similar report was found in Fall et al [3] which stated that they observed larger regression coefficients in men than in women for associations of BMI with systolic and diastolic blood pressure and levels of total cholesterol, triglycerides, alkaline transaminase, gama glutamate transaminase, and fasting insulin. Hence, men may have more risk than women.…”
Section: Discussionsupporting
confidence: 85%
“…It is commonly used algorithm to predict the risk of coronary artery diseases. It is particularly designed for adults of 20 and older patients who are not having heart disease [3]. In this tool, the following details are included which plays a major role age, gender, total cholesterol, high-density lipoprotein-cholesterol (HDL-C), smoker, systolic blood pressure, and diabetes mellitus [6,11,16,17,19].…”
Section: Nonmodifiable Risk Factors and Modifiable Risk Factorsmentioning
confidence: 99%
“…This decrease depends mainly on the peripheral vascular resistance and will represent the efficiency of the vasodilator mechanisms. 8,21,22 Corroborating the studies of Franz et al 12 we observed that changes in lifestyle are closely related to improvements in the cardiovascular system.…”
Section: Discussionsupporting
confidence: 65%
“…8,21,22 It is important to note that decreases in BP, HR and DP even in small magnitudes, promote large reductions in the rate of cardiovascular complications and general mortality. 23 The scientific literature shows that the physical exercise, present in the interdisciplinary therapy, promotes a decrease of the BP values in a chronic way.…”
Section: Discussionmentioning
confidence: 99%
“…Some covariates have an effect on our outcome of interest. It would not make sense to adjust for BMI or smoking as confounding factors, since both are included as variables in the risk estimation 31. On the other hand, it is interesting to verify whether the increased cardiovascular risk score in women with RM persists after adjustments for smoking and hypertension, or whether the results are totally dependent on these variates.…”
Section: Discussionmentioning
confidence: 99%